Age Estimation in 14-20 Years of Age by Radiological Study of Wrist Joints and Pelvic Bones (A Jaipur-Based Study) (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
Scientific estimation of age is required both in civil and in criminal cases. It is not only required in living subjects but is also required in dead bodies and even in skeletal remains to establish the identity. In living subjects, estimation of age is done by physical, dental and radiological examinations. As opinion on physical examination is inaccurate and eruption of teeth is also completed by 16 years of age (except the third molar teeth), much reliance is given to the radiological epiphyseal union of long bones. This study was carried out on 100 subjects (55 boys and 45 girls) at the S.M.S. Hospital, Jaipur. These subjects belonged to age group of 14-20 years. Their ages were confirmed by birth certificates and school records. Subjects were selected after ruling out any developmental, nutritional and endocrinal abnormalities, which affect skeletal growth. Data observed were analysed and compared with the previous studies in India and abroad.
Keywords: Age Estimation; Epiphyseal Union